PENGEMBANGAN MEDIA PEMBELAJARAN IPA BERBASIS GAMIFIKASI UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS VII DI SMP MUHAMMADIYAH CIPANAS - Ramdhani, Muhamad; Wicaksono, Dirgantara (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2025)
This study aims to develop a gamification-based science learning media on the topic "Earth and Its Satellites" to enhance the learning interest of Grade VII students at SMP Muhammadiyah Cipanas. The research background stems from the low level of student interest in science subjects and the limited availability of interactive learning media that align with the characteristics of Generation Z. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validation results indicated that the developed learning media is highly feasible, with average scores of 92% from subject matter experts, 91% from media experts, and 93% from science teachers. The practicality test showed that the media was easy to use by both teachers and students without the need for additional training. The effectiveness of the media was measured through an increase in students’ learning interest, with average questionnaire scores rising from 65.2 to 87.8. Learning outcomes also showed significant improvement, with the average pretest score of 58.4 increasing to a posttest score of 82.4, resulting in an N-Gain value of 0.58, categorized as moderate. Therefore, the gamification-based science learning media is proven to be feasible, practical, and effective in increasing students’ learning interest and outcomes.